ADDITION OF ALPHA-LIPOIC ACID IN SEMEN EXTENDER IMPROVES POST-THAW ANTIOXIDANT PROFILE AND SEMEN QUALITY OF ACHAI (BOS INDICUS) CATTLE BULLS - M. Ayaz; A. Ahmed; M. I. R. Khan; M. S. Yousaf; B. U. Din; A. Riaz (Journal of Animal and Plant Sciences, 2020)
The effect of Alpha-lipoic acid (ALA) on lipid peroxidation, catalase activity and post-thaw semen quality of Achai bulls (Bos indicus) was studied. Semen samples (n=28), collected from adult Achai bulls (n=4) at weekly intervals, were diluted with Tris-citric acid egg yolk extender having various concentrations of ALA (0.00, 0.25, 0.50, 1.00 and 2.00mM) and frozen in liquid nitrogen (-196ºC). Post-thaw semen assessment revealed that the lipid peroxidation decreased, while catalase activity increased (P<0.05) in all extenders containing ALA as compared to control, except in extender containing 2.00mM in which catalase activity decreased (P > 0.05) than control. Moreover, post-thaw semen quality parameters i.e., sperm viability and plasma membrane integrity were higher (P<0.05) in extender having 0.25 and 0.50 mM ALA compared to control, whereas mitochondrial membrane potential was significantly improved only with 0.50mM ALA as compared to control and all other ALA concentrations used. However, acrosome and DNA integrity of spermatozoa increased in extender supplemented with 0.25, 0.50 and 1.00mM ALA (P<0.05) compared to control. Computer Assisted Semen Analysis (CASA) of post-thaw semen revealed that total motility (%) and curvilinear velocity (µm/s), progressive motility (%), progressive fast motility (%) and beat cross frequency (Hz), and straight-line velocity (µm/s) and average path velocity (µm/s) were higher (P < 0.05) for 0.50 and 1.00mM, 0.25 and 0.50mM and 0.50 and 2.00mM ALA concentrations, respectively, than control. In conclusion, the addition of 0.50mM ALA in Tris-citric acid, fructose, egg yolk glycerol extender can perform optimum among all ALA concentrations (0.00, 0.25, 1.00 and 2.00mM) used, in terms of minimizing the oxidative stress and improving the post-thaw semen quality of Achai bulls.
Keywords: Bos indicus; Achai bulls; Alpha-lipoic acid; Post-thaw semen quality; Antioxidant enzyme; Computer Assisted Semen Analysis`